Dampak Gender pada Pembelian Produk Perawatan Wajah di Negara Beriklim Tropis - Raden Roro Lia Chairina; Mochammad Farid Afandi; Diddo Adding Adove; Raden Andi Sularso (Jurnal Maksipreneur, 2023)
This study aims to investigate the effect of attitudes, subjective norms, and perceived behavioral control on the purchase intention of facial care products based on the theory of planned behavior. The moderating role of gender was also tested on the relationship between purchase intention and factors from the theory of planned behavior. In addition, this research was conducted in a country with a tropical and hot climate which has many cases of facial skin problems. Data collected from 320 respondents were tested against the research model using PLS analysis. The results showed that attitudes, subjective norms, and perceived behavioral control had a significant impact on the purchase intention of facial care products, and it was also found that these factors influenced women more than men on the purchase intention of facial care products. The findings of this study present important theoretical and practical implications for the buying behavior of facial care products.